TECHNO ECONOMIC COOLING INLET AIR SYSTEM MODEL FOR DISTRICT COOLING PLANT GAS TURBINE. - SALIM, DIDI ASMARA (2020)
This research presents a study on gas turbine inlet air cooling technology for enhancement of turbine performance at Universiti Teknologi Petronas Gas District Cooling plant. Based on the ISO standard, this study found that the performance of the Gas Turbine was under-rated. And this was due to the ambient air temperature being used as the inlet of the Gas Turbine. The ISO standard temperature of a Gas Turbine should be 15oC, whereas the average temperature of the ambient is much higher. 37oC. Therefore it is necessary to decrease the inlet temperature so that the output capacity of the Gas Turbine could be increase. Using an analytical model, the performance of the gas turbine was analyzed and the size of the heat exchanger also was determined. Analysis were carried out on the assessment results of the performance which was based on the variation of the ambient throughout the year 2017